Eksplorasi Peran Gaya Kepemimpinan Dalam Mengelola Kekuasaan Dan Konflik Dalam Organisasi - Nurul Fadila; Khairunnisa Khairunnisa; Tanzila Bahar; Larasati Dwi Wahyuni; Sahraini Yamni Nurul Falah Nasution; Eka Susanti (Jurnal Pemimpin Bisnis Inovatif, 2024)
This research explores the role of leadership styles in managing power and conflict in the university environment. We employed a qualitative approach by interviewing 25 respondents from various faculties. The results indicate two categories of leadership based on Least Preference Co-worker (LPC) scores, namely High LPC person and Low LPC person. Transformational and transactional leadership styles significantly moderate power dynamics and manage conflict. Organizational factors such as structure, policies, and culture also play a crucial role in power dynamics and conflict management. In conclusion, it is essential to enhance awareness and training for university leaders to implement effective leadership approaches and improve organizational factors to create an environment conducive to collaboration and constructive conflict resolution.